PEMANFAATAN MEDIA BELAJAR PADA PELAJARAN IPA DI SEKOLAH DASAR - Widia Indah; Desi Pristiwanti; Anengsih Anengsih; Lukman Nulhakim; Suroso Mukti Leksono (Postgraduate, University of Mataram, 2023)
The purpose of this research is to know the benefits of the use of the media learned in elementary school science. The method used in this study is library research. The data-collecting techniques for the research began by looking up relevant topics to help writers in collecting data. That data is obtained by searching relevant journals, books, and resources. Research reveals that one of the key elements of the learning process is the use of the learning materials, or learning resources. Using the media is one method for improving the educational process. The teaching process in the class can be facilitated for teachers by using a media learning tool to facilitate an exchange of knowledge for students. Thus, students can learn to achieve the learning goal for this by using learning resources.